Republic of Nauru : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Nauru. (IMF Staff Country Reports; Country Report, 2022)
Early and decisive measures successfully prevented an outbreak of COVID-19 in Nauru, and as of January 2022 there have been no COVID-19 cases on the island. Strong pandemic policy measures supported the economy, which continued to expand in FY20 and FY21. Nauru's remoteness and size constrain potential growth and it is severely exposed to the negative effects of climate change on sea levels and the ocean stock of tuna. Development challenges are exacerbated by limited capacity and a high incidence of non-communicable diseases (NCDs).